PKD1 is a potential biomarker and therapeutic target in triple-negative breast cancer - Caroline Spasojevic (3619418) (2018)
Protein Kinase D1 (PKD1) is a serine/threonine kinase encoded by the PRKD1 gene. PKD1 has been previously shown to be a prognostic factor in ERα+ tamoxifen-resistant breast tumors and PKD1 overexpression confers estrogen independence to ERα+ MCF7 cells. In the present study, our goal was to determine whether PKD1 is a prognostic factor and/or a relevant therapeutic target in breast cancer. We analyzed PRKD1 mRNA levels in 527 primary breast tumors. We found that high PRKD1 mRNA levels were significantly and independently associated with a low metastasis-free survival in the whole breast cancer population and in the triple-negative breast cancer (TNBC) subtype specifically. High PRKD1 mRNA levels were also associated with a low overall survival in TNBC. We identified novel PKD1 inhibitors and assessed their antitumor activity in vitro in TNBC cell lines and in vivo in a TNBC patient-derived xenograft (PDX) model. Pharmacological inhibition and siRNA-mediated depletion of PKD1 reduced colony formation in MDA-MB-436 TNBC cells. PKD1 inhibition also reduced tumor growth in vivo in a TNBC PDX model. Together, these results establish PKD1 as a poor prognostic factor and a potential therapeutic target in TNBC. Other Information Published in: Oncotarget License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.18632/oncotarget.25292